Sr-, Zn- and Cd-exchanged zeolitic materials as water vapor adsorbents for thermal energy storage applications. (5th August 2016) - Aprea, P.; de Gennaro, B.; Gargiulo, N.; Peluso, A.; Liguori, B.; Iucolano, F.; Caputo, D.
Highlights: We prepared Sr-, Zn- and Cd-exchanged zeolitic materials as water vapor adsorbents. Water vapor adsorption isotherms at different temperatures were collected. Water vapor adsorption isotherms were modeled by means of the Dubinin equation. The isosteric heat of water vapor adsorption was successfully estimated. The specific heat storage density of the adsorbents was successfully calculated. Abstract: This paper reports the characterization of Sr-, Zn- and Cd-exchanged zeolitic materials as water vapor adsorbents, in order to evaluate the influence of the extraframework species on their adsorption properties. Both synthetic and natural substrates are taken into account. Water vapor adsorption isotherms on each ion-exchanged sample have been obtained at 298, 318, 338, and 358 K and have then been modeled using the Dubinin-Astakhov equation. Focusing on the possible implementation of such adsorbents in thermodynamic cycles, an estimation of their specific heat storage densities has been expressed. Results revealed that adsorbents of natural origin are not suitable for a valid employment in thermodynamic cycles, while FAU-type zeolite X samples exchanged with Sr 2+ or divalent transition metal ions ( i.e., Zn 2+ or Cd 2+ ) show a significant potential as heat storage media. The same trend of the specific heat storage density with the cationic content of the adsorbent can be identified for both series of synthetic and naturally originating materials ( i.e., Zn > Sr > Cd > Na), confirming how ion exchange allows effective tuning of zeolitic substrates when employed in thermodynamic cycles based on the reversible adsorption of water vapor.